The Role of Nursing in Reducing Medical Errors: Best Practices and Systemic Solutions - Albeshri , Samia Mesaf; Alharbi , Rehab Atiy; Alhawsa, Hanan zakria; Bilal, Aisha Mohammed; Alowaydhi, Bayan Yousuf; Alzahrani , Ohoud Mohammed; Fallata, Shorouq Mohammed; Almaliki, Sultan Obaidallah; Alfadly, Wedad Nwaigi; albarakati, Afnan obaidullah (Journal of Ecohumanism, 2024)
Medical errors remain a significant challenge in healthcare, contributing to patient harm and increased costs. As frontline caregivers, nurses play a pivotal role in minimizing these errors by implementing best practices and advocating for systemic improvements. This article explores the various types of medical errors and emphasizes the critical role of nursing interventions in error prevention. Key best practices discussed include effective communication strategies such as SBAR, medication management protocols, and the use of technological tools like Electronic Health Records (EHR) and Barcode Medication Administration (BCMA). Additionally, the article addresses the importance of continuous training, fatigue management, and interdisciplinary collaboration in reducing error rates. Systemic solutions are also reviewed, including fostering a culture of safety, ensuring adequate staffing, and implementing evidence-based protocols. The findings suggest that while nurses are integral to preventing errors, healthcare institutions must provide the necessary support and resources to optimize their efforts in promoting patient safety. Ultimately, the article highlights the need for both individual and organizational commitment to reducing medical errors.